Retraction notice to "Abrasive wear of zircon sand and alumina reinforced Al-4.5 wt% Cu alloy matrix composites - A comparative study" [Compos. Sci. Technol. 67 (2007) 746–751]. (20th January 2020) - Das, Sanjeev; Das, Siddhartha; Das, Karabi
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of Editors. The article duplicates significant parts of papers that had already appeared in J Mater Sci 41 (2006) 5402–5406. https://doi.org/10.1007/s10853-006-0243-0 and J Mater Sci 41 (2006) 4668–4677. https://doi.org/10.1007/s10853-006-0056-1 . One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.